Analysis of the geographical space of pre-Hispanic architectural settlements. Tangarara 3 archaeological site (Piura, Peru): Case study - Gonzalez Espino, David (2025)
The geographic spaces where pre-Hispanic architectural settlements are located have allowed us to identify the type of spatial organization of the ancient cultures that inhabited the territories of the northern coast of Peru. The founding of the city of San Miguel in 1532 is the first manifestation of the change in architecture and society. The objective of this work was to identify the founding site of the town of San Miguel among the pre-Hispanic architectural settlements. The results show that the distance between the port called La Bocana in the province of Paita and the archaeological site Tangarara 3 located in the province of Sullana is 48.80 km, which determines the identification of the site described in the chronicles. The conclusions indicate that the archaeological site Tangarara 3 is consistent with the founding event narrated in the chronicles, verified by data collected from the writings of Francisco de Xerez.